Systemic lupus and catastrophic antiphospholipid syndrome manifesting as cardiogenic shock. (October 2019) - Schultz, M; Wimberly, K; Guglin, M
In this case series we present two young female patients presenting in the peripartum period with cardiogenic shock. Both patients had underlying autoimmune diseases, one with systemic lupus erythematosus (SLE) and the other with antiphospholipid syndrome (APS). In both cases cardiogenic shock was a direct manifestation of their autoimmune condition, and with prompt diagnosis and management both patients were able to recover. This case series illustrates the importance of early recognition of cardiogenic shock as a rare manifestation both of SLE and APS.